2017
DOI: 10.1007/s12031-017-0888-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stereotactic Injections on Demyelination and Remyelination: a Study in the Cuprizone Model

Abstract: Remyelination is the natural repair mechanism in demyelinating disorders of the central nervous system (CNS) such as multiple sclerosis. Several animal models have been used to study demyelination and remyelination. Among toxic animal models, oral administration of the toxin cuprizone leads to white and gray matter demyelination. In contrast, focal demyelination models include the stereotactic application of a toxin such as lysolecithin or ethidium bromide. The injection procedure generates a local disruption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
3
17
1
Order By: Relevance
“…Notably, the CD8 signal was also detected in brain and spinal cord tissue by western blot analysis when Cx was combined with 0.1% CPZ and PT. This preferential increase in CD8 levels was not observed in previous CPZ-feeding studies that did not include strategies to protect the peripheral immune system (Remington et al, 2007;Partridge et al, 2016;Traka et al, 2016;Tejedor et al, 2017;Sen et al, 2019a) or which the focus of analysis was on a pan T-cell marker (CD3; Caprariello et al, 2018). While it has been argued that ''cellular sources of CD8 were reactive macrophages/microglia'' (Zhang et al, 2009), here, double labeling of the brain and spinal cord sections with IBA 1 and CD8 showed distinct microglia and CD8 cell populations.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Notably, the CD8 signal was also detected in brain and spinal cord tissue by western blot analysis when Cx was combined with 0.1% CPZ and PT. This preferential increase in CD8 levels was not observed in previous CPZ-feeding studies that did not include strategies to protect the peripheral immune system (Remington et al, 2007;Partridge et al, 2016;Traka et al, 2016;Tejedor et al, 2017;Sen et al, 2019a) or which the focus of analysis was on a pan T-cell marker (CD3; Caprariello et al, 2018). While it has been argued that ''cellular sources of CD8 were reactive macrophages/microglia'' (Zhang et al, 2009), here, double labeling of the brain and spinal cord sections with IBA 1 and CD8 showed distinct microglia and CD8 cell populations.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, western blot analysis confirmed that Cx countered all CPZ-induced suppression of CD4/8 signal in the thymus and spleen. In the absence of the protective effects of Cx, the direct effects of CPZ-feeding on the thymus and spleen provide a plausible explanation as to why prior studies did not show the involvement of T-cells in the CNS of CPZ-fed mice (Remington et al, 2007;Tejedor et al, 2017;Sen et al, 2019a). Likewise, the demonstration that CPZ ameliorates and/or prevents the clinical and pathological features of EAE and Theiler's virus FIGURE 7 | Detection of CD4/8 signals in the CNS homogenate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the marked CNS oligodendrocytosis, demyelination, and gliosis in CPZ-fed mice, no involvement of adaptive immune cells in the CNS lesions was found (82, 86). However, T-cell infiltration into the CNS was not evident even when the BBB was disrupted by injection of ethidium bromide, lysolecithin (86), or pertussis toxin (82). This indicated the presence of an alternative mechanism(s) in the adaptive immune cell response in the CPZ model, independent of BBB integrity or the lymphatic system.…”
Section: Cpz Model: Relevance To Modeling Msmentioning
confidence: 99%
“…In order to clarify the role of intracellular PN in BBB permeability in vivo, MF and MT stabilizers were used to restore intracellular PN levels in an adult male SD rat BBB lesion model; the schematic diagram of the experiment is shown in Fig. 7A [31,32] . The SD rats were injected with Evans Blue (EB).…”
Section: Inhibition Of Pn Production Could Block Nonselective Bbb Permentioning
confidence: 99%